Influence of Exercise Mode on Post-exercise Arterial Stiffness and Pressure Wave Measures in Healthy Adult Males - Pierce, Doris R.; Doma, Kenji; Raiff, Hayleigh; Golledge, Jonathan; Leicht, Anthony S. (Frontiers in Physiology, 2018)
Background: Exercise mode has been reported to be an important determinant of arterial stiffness and wave reflection changes following a brief bout of exercise with inconsistent results to date. This study examined the impact of exercise mode on arterial stiffness and pressure wave measures following acute aerobic exercise (AER), resistance exercise (RES), and a control (CON) condition with no exercise. Methods: In a randomized, cross-over, repeated measures design, 21 healthy adult males (26.7  7.2 years) undertook three experimental intervention sessions: AER (30-minute cycle ergometry at 70-75% maximum heart rate), RES (3x10 repetitions of six upper and lower body exercises at 80-90% of 10-repetition maximum) and CON (30-minute seated rest). Measures of arterial stiffness and pressure waves, such as carotid-femoral pulse wave velocity (cf-PWV), augmentation index (AIx), AIx corrected for heart rate of 75 (AIx75), and forward wave (Pf), backward wave (Pb) and reflection magnitude, were assessed at Rest and at 10-minute intervals for 60 minutes after the intervention sessions. Comparisons between interventions and over time were assessed via repeated measures ANOVA and post-hoc Tukeys tests. Results: No significant differences in cf-PWV were noted between the three interventions at rest or post-intervention. However, RES led to significantly greater post-intervention AIx, AIx75, Pf, and Pb compared to AER and CON with AIx75 also remaining significantly elevated throughout the post-intervention period. In contrast, AER resulted in a brief, significant elevation of AIx75 and no change in cf-PWV, Pf, Pb, and reflection magnitude. Conclusions: Exercise mode, specifically RES and AER, significantly influenced the time course of pressure wave reflection responses following a brief bout of exercise in healthy adult males. Distinct adjustments during exercise including changes in blood pressure and vasomotor tone may be key modulators of post-exercise arterial function. Identification of modal differences may assist in understanding the impact of exercise on cardiovascular function and the mechanisms by which exercise benefits vascular health.